Treatment outcomes for idiopathic sudden sensorineural hearing loss in dialysis patients - Seonju Kim; Dong Kyu Lee; Hae-rim Kim; Jung Mee Park; Soon Bae Kim; Hoon Yu (Scientific Reports, 2024)
Abstract Idiopathic sudden sensorineural hearing loss (ISSNHL) is challenging for both nephrologists and otolaryngologists treating patients undergoing dialysis. This single-center, retrospective, observational study investigated the treatment outcomes of patients with ISSNHL undergoing dialysis, enrolling 700 patients (47 undergoing and 653 not undergoing dialysis) diagnosed with ISSNHL between January 2005 and December 2021 at Asan Medical Center, Republic of Korea. To balance pre-existing clinical characteristics, 1:5 propensity score matching (PSM) was performed with the patients who were not undergoing dialysis. Treatment included high-dose systemic steroid therapy or intra-tympanic steroid injections. The pure tone average of the groups was compared before and 2 weeks and 2 months after treatment. The hearing-improvement degree was evaluated using Siegel's criteria. Before PSM, age, prevalence of diabetes or hypertension, initial hearing threshold at each frequency level (0.5, 1, 2, and 4 kHz), and treatment strategies exhibited significant between-group differences. However, in the PS-matched cohort, none of the confounders showed significant between-group differences. Two months after steroid treatment, the non-dialysis patient group demonstrated significantly higher average improvement in pure tone audiometry (P = 0.029) and greater percentage of complete response according to Siegel's criteria. This study suggests that treatment outcomes for ISSNHL are significantly poorer for patients undergoing than for those not undergoing dialysis.